Objective-C for Absolute Beginners iPhone, iPad and Mac Programming Made Easy - Bennett, Gary (Apress, 2011)
It seems as if everyone is writing applications for Apple’s iPhone and iPad, but how do they all do it? It’s best to learn Objective-C, the native language of both the iOS and Mac OS X, but where to begin? Right here, even if you’ve never programmed before!